Opportunities in Indian Derivatives and Commodities Market - Verma, Sanjeev; Chauhan, Rohit (Indian Journal of Finance, 2008)
Derivatives market has got a tremendous potential by giving options of hedging speculation and arbitration. Indian market which is still a naïve compared to international market has got a high potential in this field due to boom in sensex and Increase in Amount of FIIs spending in the market. In addition to this the beta of Sensex is high in relation to international markets which again gives high opportunities for Indian investors of speculating in this market. This paper writes about the opportunities and recommendations in today's Indian derivative market in comparison to their international counter parts. This paper also touches the Commodity market in India and points out the potential prospects in this segment.